Effect of pyrolysis temperature on the chemical oxidation stability of bamboo biochar. (October 2016) - Chen, Dengyu; Yu, Xinzhi; Song, Chao; Pang, Xiaoli; Huang, Jing; Li, Yanjun
Highlights: Carbon yield of biochar decreased from 71.72% to 38.48% as the temperature increased. The chemical oxidation stability of biochar was determined using the K2 Cr2 O7 method. The aromatization degree of biochar increased with increasing pyrolysis temperature. Carbon loss proportion decreased from 16.52% to 6.69% with increasing temperature. Biochar showed better stability at a higher temperature in the range 300–700 °C. Abstract: Biochar produced by biomass pyrolysis has the advantage of carbon sequestration. However, some of the carbon atoms in biochar are not very stable. In this study, the effect of pyrolysis temperature on the chemical oxidation stability of bamboo biochar was investigated using the atomic ratios of H/C and O/C, Fourier transform infrared spectroscopy, and potassium dichromate (K2 Cr2 O7 ) oxidation spectrophotometric method. The results show that the carbon yield and ratios of H/C and O/C decreased from 71.72%, 0.71, and 0.32 to 38.48%, 0.22, and 0.06, respectively, as the temperature was increased from 300 °C to 700 °C. Moreover, the main oxygen-containing functional groups gradually decreased, while the degree of aromatization increased accordingly. The biochar showed a better stability at a higher pyrolysis temperature. The proportion of carbon loss, i.e., the amount of oxidized carbon with respect to the total carbon of the biochar, decreased from 16.52% to 6.69% with increasing temperature.